Rescuing the Gospel from the cowboys a Native American expression of the Jesus way - Twiss, Richard 1954-2013 (Downers Grove, Ill. InterVarsity Press Books, 2015)
"The gospel of Jesus has not always been good news for Native Americans. But despite the far-reaching effects of colonialism, some Natives have forged culturally authentic ways to follow Jesus. In his final work, Richard Twiss surveys the complicated history of Christian missions among Indigenous peoples and voices a hopeful vision of contextual Native Christian faith"--Provided by publisher
"The gospel of Jesus has not always been good news for Native Americans. But despite the far-reaching effects of colonialism, some Natives have forged culturally authentic ways to follow Jesus. In his final work, Richard Twiss surveys the complicated history of Christian missions among Indigenous peoples and voices a hopeful vision of contextual Native Christian faith"--Provided by publisher
In memoriamThe creator's presence among Native People -- The colonization, evangelization, and assimilation of First Nations People -- Sweating with Jesus : stories of the Native experience -- A view from the hill : emerging Native expressions of the Jesus way -- From colonization to contextualization -- Looking down the road : the future of the Native church -- Editors' tribute to Richard Twiss -- Appendix A: Final words on Indigenous education and theology -- Appendix B: What should we call you? -- Glossary.
Includes bibliographical references (pages 262-271)
Keywords: Indians of North America -- Missions -- History; Indians of North America -- Religion; Indians of North America -- Canada -- Religion; Christianity -- United States; Christianity -- Canada